Green ICT for better human life - Hameed, Shihab A. (2016)
Abstract—Seven decades of rapid development in computing and ICT make it an efficient and effective driving force toward better human life. ICT industry has an appreciated contribution to the global economy associating with innovation, invention and rapid development of almost all the aspect of human life (Education, Health, Industry, Entertainment, Agriculture, Business, etc.). On the other hand, global environment and human life facing serious challenges related to human health and life style, climate change and global warming, and unwise consumption and management of resources. The diversity and rapid increasing of ICT usage in our life leads to more energy consumption and environmental problems, which has negative impact on economy, human health, and life style. The expected ICT consumption of energy for the next few years will be about 15% of the total consumption worldwide. This make ICT industry shared responsibility for global CO2 emissions and environmental problems. Therefore, many developed countries are establishing Green ICT policies and strategies to eliminate environmental and human health problems. Shortage and weakness of Green ICT policies or strategies in developing countries requires adoption of an effective one that leads to wise ICT usage and energy consumption. Ethical and moral values should integrate with technical aspects to have effective strategies for green ICT that leads to better human life.